Long-term market implications of data breaches, not. Issue 4 (2nd October 2017) - Lange, Russell; Burger, Eric W.
ABSTRACT: This report assesses the impact disclosure of data breaches has on the total returns and volatility of the affected companies' stock, with a focus on the results relative to the performance of the firms' peer industries, as represented through selected indices rather than the market as a whole. financial performance is considered over a range of dates from 3 days post-breach through 6 months post-breach, in order to provide a longer-term perspective on the impact of the breach announcement.